2011
DOI: 10.1166/asl.2011.1915
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Synthesis of Silver Nanoparticles by Streptomyces glaucus and Spirulina platensis

Abstract: Microbial synthesis of nanoparticles has a potential to develop simple, costeffective and eco-friendly methods for production of technologically important materials. In this study, for the first time a novelactinomycete strain Streptomyces glaucus71 MD isolated from a soy rhizosphere in Georgiais for the first time extensively characterized and utilized for the synthesis of silver nanoparticles. Scanning Electron Microscope (SEM) allowed observing extracellular synthesis of nanoparticles, which has many advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…The UV-Vis spectra of absorbance at concentrations of 10 -3 M of gold and silver compounds and different reaction time are given in Figures 1a and 1b, respectively [17,18]. In these figures, the peak intensity for nanoparticles of specific sizes increased as a function of the reaction time.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The UV-Vis spectra of absorbance at concentrations of 10 -3 M of gold and silver compounds and different reaction time are given in Figures 1a and 1b, respectively [17,18]. In these figures, the peak intensity for nanoparticles of specific sizes increased as a function of the reaction time.…”
Section: Resultsmentioning
confidence: 93%
“…The synthesis of silver and gold nanoparticles by the biomass of S. platensis was studied in [17] and [18], respectively. The present work is a continuation of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to bacteria and fungi, actinomycetes are known to secrete much higher amounts of enzymes, proteins, small molecules with reducing properties and secondary metabolites, and thereby it significantly enhances the biosynthesis of metal nanoparticles. In addition, as a prokaryote, actinomycetes can be easily subjected to genetic manipulations which help in the future to achieve better control over size and polydispersity of the nanoparticles (Tsibakhashvili et al 2011). It is observed that the time required for the completion of nanoparticle synthesis using both bacteria (Klaus et al 1999) and fungi (Mukherjee et al 2002) ranges between 24 and 120 h, whereas actinomycetes can be achieve in 24 h of incubation (Sadhasivam et al 2010).…”
Section: Biological Synthesis Of Nanoparticles Using Actinomycetesmentioning
confidence: 99%
“…BDUKAS10, an isolate of mangrove sediment (Sivalingam et al 2012), Streptomyces hygroscopicus isolated near the Pacific shore region (Sadhasivam et al 2010), Streptomyces sp. LK3 isolated from marine sediments (Karthik et al 2014), Streptomyces glaucus 71 MD isolated from a soybean rhizosphere (Tsibakhashvili et al 2011), Streptomyces sp. (09 PBT 005) 09 PBT 005 isolated from sugarcane rhizosphere soil (Saravanakumar et al 2014) and an antagonistic Streptomyces sp.-SBU3 isolated from terrestrial red garden soil from groundnut (Krishnakumar and Bai 2015).…”
Section: Biological Synthesis Of Nanoparticles Using Actinomycetesmentioning
confidence: 99%
“…Some results of earlier investigations are presented in Refs. [26,27]. Strains of microorganisms belonging to Streptomyces and Arthrobacter genera have been studied as possible "nanofactories" for the development of clean and nontoxic methods of the synthesis of silver and gold nanoparticles.…”
mentioning
confidence: 99%